Study the influence of hydraulic shock absorber bidirectional ratio on dynamic performance of locomotive - ZHANG Xin; LI Jianwei; SHI Qinglu; LI Xingren; WANG Yu (机车电传动)
In order to study the influence of bidirectional ratio of hydraulic shock absorber in locomotive suspension system on locomotive dynamic performance, a vehicle dynamic model with 90 degrees of freedom was established by using Simpack software, which consisted of body, frame, wheelset etc. The nonlinear damping characteristics of shock absorber were embedded. Under random excitation of AAR 5 track spectrum, the locomotive dynamic performance corresponding to the damping model with two-way ratio of shock absorber greater than, equal to and less than 1 was simulated and analyzed respectively. The results show that: When the bidirectional ratio of primary vertical shock absorbers is 1, the vertical Sperling stability index of the locomotive under linear working condition is 3.08, and the maximum acceleration power spectral density is 0.11 m2/s3, both of which are smaller than the damping model with bidirectional ratio not 1, and the vibration transmission to the car body is more effectively attenuated. The vertical dynamic load coefficients of the primary and secondary suspension systems are minimum when the bidirectional ratio of the shock absorber is equal to 1, but they are not minimum when the vehicle speed is greater than 100 km/h. For the damping model with bidirectional ratio of 1, the anti-derailment coefficient of the locomotive and the vertical dynamic load coefficient of the secondary suspension device under curving conditions are better than that with bidirectional ratio greater than 1 or less than 1, but the vertical dynamic load coefficient of the primary suspension device is the largest. When the bidirectional ratio of the secondary transverse shock absorber is 1, the maximum nonlinear critical speed of the locomotive reaches 263 km/h, which is higher than that when the bidirectional ratio is greater than or less than 1. The research can provide some reference for the design of locomotive suspension system.